Large easy-axis magnetic anisotropy in a series of trigonal prismatic mononuclear cobalt(ii) complexes with zero-field hidden single-molecule magnet behaviour: the important role of the distortion of the coordination sphere and intermolecular interactions in the slow relaxation. Issue 12 (7th April 2022) - Landart-Gereka, Aritz; Quesada-Moreno, María Mar; Díaz-Ortega, Ismael F.; Nojiri, Hiroyuki; Ozerov, Mykhaylo; Krzystek, J.; Palacios, María A.; Colacio, Enrique
Abstract : A N6 -tripodal ligand allows the preparation of a family of prismatic mononuclear cationic Co II complexes with SMM behavior. Their axial anisotropy, magnetic relaxation and hysteresis width are modulated by the anion effects on the crystal structure. Abstract : The complexes [Co(L)]X·S (X = CoCl4 2−, S = CH3 CN (1 ); X = ZnCl4 2−, S = CH3 OH (2 )), [Co(L)]X2 ·S (X = ClO4 −, S = 2CH3 OH (3 ) and X = BF4 − (4 )) and [Co(L)(NCS)2 ] (5 ), where L = the N6 -tripodal ligand tris(pyridylhydrazonyl)phosphorylsulfide, were prepared and studied by X-ray crystallography, ac and dc magnetic data, FIRMS and HFEPR spectra, and theoretical calculations. On passing from 1 to 4, the change of the counteranion decreases slightly the distortion of the CoN6 coordination polyhedron from trigonal prismatic to octahedral, with a parallel increase of the easy-axis magnetic anisotropy. Compound 1 does not show slow magnetic relaxation, even in the presence of a dc magnetic field, due to fast QTM triggered by dipolar interactions. Although the complexes 2–4 show a weak frequency and temperature dependence of the ac susceptibility below 10 K at zero field, they exhibit slow relaxation and single-molecule magnet (SMM) behaviour under the corresponding optimal field. The relaxation of the magnetization takes place mainly through a Raman relaxation process above 4 K, whereas below this temperature QTM and/or direct processes dominate. The relaxation time increases with the parallel increase of the uniaxial anisotropy on passing from 1 to 4 . The width of the hysteresis for the trigonal prismatic complexes at 0.4 K decreases in the order 3 > 2 > 4 > 1, which is due to combined effects of QTM relaxation and axial anisotropy. Magnetic dilution of complexes 3 and 4 with Zn II triggers the slow relaxation of the magnetization at zero-field, so that these complexes can be considered as "hidden mononuclear SMMs". Compound 5, with a compressed octahedral geometry, exhibits easy-plane magnetic anisotropy ( D = +34.7 cm −1 ), and it is a field-induced mononuclear SMM with magnetization relaxation faster than compounds 2–4 and a smaller hysteresis loop.